2005
DOI: 10.1016/j.allerg.2005.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of asthma in schoolchildren in Portuguese speaking regions

Abstract: Asthma in schoolchildren became a priority both for developing and developed countries. Two large multi-centre epidemiological studies (Portuguese Study of Allergic Diseases in Childhood and the International Study of Asthma and Allergies in Childhood) were implemented in the last decade. One of the main objectives was to compare prevalence of asthma and evaluate cultural, ethnic and environmental variables in schoolchildren of different continents. These studies can contribute to a global strategy (with natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In Portugal, 7.83% of the population is affected by clinical asthma and 8.72% by wheezing symptoms [ 5 ]. Within Portugal, the island of Madeira has a high prevalence of the disease, as active asthma (presence of symptoms during the last 12 months) affects 14.6%, and atopy (positive reaction to skin prick tests (SPT) to common aeroallergens and the presence of specific IgE) affects 54% of the population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Portugal, 7.83% of the population is affected by clinical asthma and 8.72% by wheezing symptoms [ 5 ]. Within Portugal, the island of Madeira has a high prevalence of the disease, as active asthma (presence of symptoms during the last 12 months) affects 14.6%, and atopy (positive reaction to skin prick tests (SPT) to common aeroallergens and the presence of specific IgE) affects 54% of the population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence of asthma in the Madeira population [ 6 ], determining the population’s genetic background is an essential first step towards understanding the mechanisms of the disease. In previous work [ 7 ] we showed that both IL4-590 and IL4-RP2 are useful genetic markers to detect asthma predisposition in the Madeira population.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades tourism has supplanted the production of salt as the main activity (PINTO; ALMEIDA, 2005). During this period the population has increased greatly, due basically to the development of modern tourist resorts, based mainly on the town of Santa Maria on the southern tip of the island which has become the main tourist centre of the archipelago.…”
Section: Study Areamentioning
confidence: 99%